Pengaruh Penempatan Kerja Terhadap Kinerja Pegawai Pada Dinas Kesehatan Kabupaten Soppeng - Sumarno Sumarno; Yusran Yusran; Marayuni Marayuni (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This study aims to determine the magnitude of the effect of work placement on employee performance at the Soppeng District Health Office, using a quantitative research approach survey type. Employee Placement is one of the variables that plays a major role in determining Employee Performance. The right placement according to the ability of employees is one of the supports for increasing performance at the Soppeng District Health Office. The results of this study indicate that work placement has a positive and significant effect on employee performance at the Soppeng District Health Office. These results show that the level of acquisition of the Job Placement and Employee Performance variables is on average good with an ideal score.